PENTINGNYA KEMAMPUAN BERKOMUNIKASI SECARA EFEKTIF DALAM SUPERVISI HOTEL - Gri Sella Febriani; Ni Made Putri Intan Sanjiwani; I Gusti Ayu Melistyari Dewi (MSJ : Majority Science Journal, 2023)
The importance of communication in hotel supervision greatly influences employees so they can work in accordance with directions and regulations. Effective communication will provide understanding to employees so that mistakes do not occur at work, of course it will also have a positive impact on the work environment and working in a team will form cohesiveness between members, therefore it’s important to carry out good communication. This research aims to analyze the task of a supervisor to direct and guide team communication so that it can improve the performance process of each employee at work.